Guideline on Leadership Development Based on Kalyanamittadhamma for School Administrators of Pom Nagaraj Sawathayanon School Under the Secondary Educational Service Area Office 6 - ก่อวุฒิกุลรังสี ปิยะดา; ศิริวรรณ อินถา; หุ่นวิไล วิชชุดา (Journal of Educational Review Faculty of Education in MCU, 2018)
The objectives of this research were; 1. To study a guideline on leadership development based on Kalyanamittadhamma for school administrators of Pom Nagaraj Sawathaynon School under the Secondary Educational Service Area Office 6, 2. Study the use of Kalyanamittadhamma of school administrators of Pom Nagaraj Sawathaynon School under the Secondary Educational Service Area Office 6, and 3. To propose a guideline on leadership development based on Kalyanamittadhamma for school administrators of Pom Nagaraj Sawathaynon School under the Secondary Educational Service Area Office 6. The mixed research methodology was used in the study. The qualitative data were collected by interviews with 7 school teachers and administrators while the quantitative data were obtained from 77 school teachers and administrators through questionnaires. The questionnaires were tried out with teachers and administrators with IOC value at 1.00 and confidence value at 0.829. The data were analyzed by percentage, mean and standard deviation. The results of the study showed that: 1. The opinion of teachers and administrators towards the use of Kalyanamittadhamma of school administrators of Pom Nagaraj Sawathaynon School under the Secondary Educational Service Area Office 6 was at the high level overall. In aspect, the highest level was on Never exhorting groundlessly, followed by Loveable, Being a counselor, and Adorable respectively. 2. The guidelines on leadership development based on Kalyanamittadhamma are as follows; 1) Loveable; to have a good habit, a good character, neat and tidy clothes, kind and friendly, and hospitality 2) Respectable; to have suitable behaving,patient in situations, and moral and ethics 3) Adorable; to have the real knowledge and skills in work, democratic idea and modern up-date knowledge 4) Being a counselor; knowing how to express idea, approach others, assign the work, and plan to improve the work 5) Being a patient listener; being ready to listen to different ideas, patient to situations, and to build administrative network and teamwork 6) Able to treat profound subjects; to have ability in clarify the profound subjects to others, vision in administration, and public relations 7) Never exhorting groundlessly; to remain on morality and ethics